Airway Malacia: Clinical Features and Surgical Related Issues, a Ten-Year Experience from a Tertiary Pediatric Hospital - Michele Ghezzi; Enza D'Auria; Andrea Farolfi; Valeria Calcaterra; Alessandra Zenga; Annalisa De Silvestri; Gloria Pelizzo; Gian Vincenzo Zuccotti (MDPI AG, 2021)
Background: Few studies have been carried out with the aim of describing the clinical course and follow-up of patients with tracheomalacia. We aim to describe the symptoms at diagnosis and the post-treatment clinical course of patients affected by airway malacia. Methods: We retrospectively analyzed characteristics of pediatric patients with a diagnosis of airway malacia. Patients were classified into three groups: bronchomalacia (BM), tracheomalacia (TM) and tracheo-bronchomalacia (TBM). Demographic and clinical data, diagnostic work-up and surgical treatment were recorded. Results: 13/42 patients were affected by congenital syndromes (30.9%). Esophageal atresia with or without tracheal-esophageal fistula (EA/TEF) was detected in 7/42 patients (16.7%). Cardiovascular anomalies were found in 9/42 (21.4%) and idiopathic forms in 13/42 (30.9%). BM occurred in 7/42 (16.6%), TM in 23/42 (54.7%) and TBM in 12/42 (28.6%). At the diagnosis stage, a chronic cough was reported in 50% of cases with a higher prevalence in EA/TEF (p = 0.005). Surgery was performed in 16/42 (40%) of children. A chronic cough and acute respiratory failure were correlated to the need for surgery. During follow-up, there was no difference in persistence of symptoms between conservative vs surgical treatment (p = 0.47). Conclusion: the management of tracheomalacia remains a challenge for pediatricians. Clinical manifestations, such as a barking cough and acute respiratory failure may suggest the need for surgery. Follow-up is crucial, especially in those patients affected by comorbidities, so as to be able to manage effectively the possible persistence of symptoms, including those that may continue after surgical treatment.